2008
DOI: 10.1074/mcp.m700084-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Proteomics Study Reveals That N-Acetylglucosaminyltransferase V Reinforces the Invasive/Metastatic Potential of Colon Cancer through Aberrant Glycosylation on Tissue Inhibitor of Metalloproteinase-

Abstract: Cancer is a very complicated process, characterized by the uncontrolled, unbalanced overgrowth of malignant cells. The complexity of oncogenic processes and cancer progressions has demanded the discovery of biomarkers with a high sensitivity and specificity for diagnosis, prognosis, diseases monitoring, and therapeutic response prediction. Unfortunately, a discrete biomarker for colon cancer has yet to be discovered, although nearly 800,000 new colorectal cancer cases are thought to globally occur each year, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 45 publications
6
69
1
Order By: Relevance
“…Ko's group reported that TIMP-1 is also a target molecule against GnT-V and plays a key role in cancer metastasis. They also found that TIMP-1 was aberrantly glycosylated by GnT-V showed a weaker inhibition with respect to both matrix metalloproteinase (MMP)-2 and MMP-9, and this aberrancy was closely associated with cancer cell invasion and metastasis in vivo as well as in vitro (72). As described above, GnT-V and GnT-III have adverse effects in cancer invasion and metastasis (5,6,(23)(24)(25)(26).…”
Section: β1-6glcnac Branch and Gnt-vmentioning
confidence: 89%
“…Ko's group reported that TIMP-1 is also a target molecule against GnT-V and plays a key role in cancer metastasis. They also found that TIMP-1 was aberrantly glycosylated by GnT-V showed a weaker inhibition with respect to both matrix metalloproteinase (MMP)-2 and MMP-9, and this aberrancy was closely associated with cancer cell invasion and metastasis in vivo as well as in vitro (72). As described above, GnT-V and GnT-III have adverse effects in cancer invasion and metastasis (5,6,(23)(24)(25)(26).…”
Section: β1-6glcnac Branch and Gnt-vmentioning
confidence: 89%
“…Aberrant protein glycosylation has been observed during cancer development and progression and the pathological implications of aberrant glycosylation have been elucidated in several functional studies (2,(21)(22)(23). One of the best characterized features is the role of aberrant glycans of tissue inhibitor of metalloproteinase-1 during invasion of colon cancer cells (2).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best characterized features is the role of aberrant glycans of tissue inhibitor of metalloproteinase-1 during invasion of colon cancer cells (2). The tetra-antennary adducts created by GnT-V play an interfering role in the tissue inhibitor of metalloproteinase-1/gelatinases interactions, thereby resulting in elevated gelatinase activity and enhanced invasive potential in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant glycosylation is a functional marker that can be used to gauge the clinic-pathogenic process in cancer. This notion is well illustrated by the functional role of the aberrant tissue inhibitor of metalloproteinase-1 (TIMP-1) in cancer invasion and metastasis (38). TIMP-1 is an endogenous glycoprotein which inhibits several matrix metalloproteinases (MMPs) in a 1:1 stoichiometric manner, and is known to regulate cancer metastasis.…”
Section: Alterations In the Glycosylation Status Associated With Cancermentioning
confidence: 99%